The Rice Availability and Basic Food Consumption of Farming Households in Padengo Village Dengilo Subdistrict Pohuwato Regency Gorontalo Province - Indriyani Saidi; Yuliana Bakari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Food security must be achieved because food is one of the issues that need to be addressed at the individual and household levels, particularly in terms of meeting consumption needs that lead to adequate food availability. The objectives of this study are (1) to analyze the availability of food (rice) in farmer households and (2) to analyze the consumption patterns of staple foods in farmer households. The study was conducted from May to August 2024, using purposive sampling, with the Harry King nomogram formula and a 91% confidence level for the sample relative to the population. With a margin of error of 9% from the total population of 191, resulting in 60 rice farmers. The types and sources of data include primary data obtained through field surveys conducted in Padengo Village via interviews using questionnaires, as well as secondary data obtained from the Pohuwato Central Statistics Agency. Data analysis employed consumption pattern analysis using the Food Recall method and assessed the food availability of staple foods. The analysis involved two key components: Input (sources of staple foods from production, purchases, and food assistance) and Output (sold, used in social activities, or given to others). The results of this study indicate that the average food consumption pattern of farmer households in Padengo Village is 1,743 kcal/person/day, which is below the recommended energy sufficiency level of 2,100 kcal/person/day. Furthermore, the availability of staple food rice in farmer households, as seen from the household food consumption pattern, was 1,127 kcal/person/day, which is below the recommended level of 1,400 kcal/person/day.